EP469 Sentınel lymph node biopsy in early stage endometrial cancer: a turkısh gynecologıc oncology group study (TRSGO-SLN-001). (1st November 2019) - Taşkın, S; Altın, D; Vatansever, D; Tokgözoğlu, N; Karabük, E; Turan, H; Takmaz, Ö; Kahramanoğlu, İ; Naki, M; Taşkıran, Ç; Güngör, M; Köse, F; et al.
Abstract : Introduction/Background: This multicentric study aimed to evaluate feasibility of sentinel lymph node (SLN) mapping in clinically uterine-confined endometrial cancer. Methodology: Indocyanine green (ICG) or blue dye was used as tracer ICG was injected to the uterine cervix and blue dye was injected to uterine cervix or fundus. SLN and/or suspicious lymph nodes were resected. Side specific lymphadenectomy was performed when mapping was unsuccessful. Results: 357 eligible patients were analysed. The median resected SLN number was 3 per patient. Laparoscopic, open and robotic surgery was performed in 225 (63%), 93 (26.1%) and 39 (10.9%) of the patients, respectively. ICG was used in 231 (64.7%) and blue dye in 126 (35.3%) patients. Dyes were injected into the cervix in 355 (99.4%) patients. In 71 (19.9%) patients only SLN biopsy was done whereas 169 (47.3%) underwent pelvic and 117 (32.8%) underwent pelvic and paraaortic lymphadenectomy. The overall, unilateral and bilateral SLN detection rates were 91.9%, 20.7%, 71.1%, respectively. These rates were 91.2%, 17.4% and 73.8% by using ICG and 92.2%, 22.5% and 69.7% by using blue dye. There is no statistical significance (p=0.526). In 29 of 358 (8%) patients there was no lymph node in resected tissue labelled as SLN (empty packets). There were 40 (11%) patients with lymphatic metastasis. SLN was found metastatic in 32 of 40 patients and 14 of them also had metastasis in non-SLN(s). 4 of 40 cases were diagnosed by side specific lymphadenectomy. However, SLN algorithm were not able to detect 4 of 40 metastatic patients. NPV, sensitivity and false negative rates were 98.4%, 88.8% and 1.57%, respectively. Conclusion: SLN biopsy has high accuracy in detecting lymphatic metastasis. However nearly half of the cases with metastatic SLN(s) also had non-SLN involvement and the effect of leaving these nodes in situ on survival should be evaluated. To avoid 'empty packet' on final pathology, intraoperative frozen section evaluation could be suggested. Disclosure: Nothing to disclose.